Management of safflower aphid through seed treatment and foliar sprays: Management of safflower aphid through seed treatment and foliar sprays - P S SRINIVAS (Journal of Oilseeds Research, 2020)
Seed treatment with either thiamethoxam 30FS @ 10 ml/kg (4.6-5.2 aphids/5cm twig/plant) or imidacloprid 600 FS @ 8 ml/kg (1.1-2.1 aphids/5cm twig/plant) protected the crop from aphid infestation up to 40 days compared to untreated plots (41.1-42.3 aphids/5cm twig/plant). Treatments viz., seed treatment with imidacloprid + spray with dimethoate @1000 ml/ha; or seed treatment with thiamethoxam + spray with pymetrozine @ 300g/ha; or seed treatment with imidacloprid + spray with pymetrozine @ 300g/ha recorded significantly lower aphids and resulted in significantly higher seed yields.